UJI KESAHIHAN INTERNA DAN KEHANDALAN KUESIONER CABIN FEVER PHENOMENON (CFP) VERSI INDONESIA - Firmansyah, Yohanes; Su, Ernawati; Buntara, Ivan; Hendsun, Hendsun; Sutjipto, Fiolita Indranita; Setiyati, Pinka Nurashri (Universitas Tarumanagara, 2020)
Outbreaks and isolation due to at home due to COVID-19 outbreaks may have many psychological consequences on human life. Psychological consequences that are not detected early can cause problems in the future that can disrupt the lives of families and sufferers, therefore the need for screening tests that are accurate and reliable in detecting the appearance of psychiatric symptoms during isolation.The survey research was carried out virtually via Google Form This method was chosen because of the condition of Large Scale Social Restrictions due to the Covid-19 Pandemic, which made it impossible to conduct face-to-face interviews. The sample of this research is all of the productive age community with exclusion criteria in the form of incomplete data or unwilling to join the research. This research is a preliminary study of a series of validity and reliability test processes. Internal validity test analysis using the Pearson Product Moment method with the interpretation of the questions is said to be valid if the correlation rho (r) ≥ 0.3. Analysis of reliability testing using the Cronbach α test method with reliable interpretation if the minimum value of Cronbach α is 0.6. 281 respondents who met the inclusion criteria. The results of testing with Pearson Product Moment or Pearson Correlation obtained the value of rho (r) in all questions is above 0.3. The reliability test results using the Cronbach α test are 0.935 with the Cronbach's Alpha if Item Deleted value on each grain below the Cronbach α value. Cabin Fever Phenomenon (CFP) Indonesian Version is proven to have good validity and excellent reliability to detect the appearance of psychiatric symptoms during isolation. Further validity testing is needed such as an external validity test Keywords: Cabin Fever Phenomenon; COVID-19; psychiatry; validity and reliability ABSTRAKWabah dan isolasi akibat dirumah akibat dari wabah COVID-19 mungkin memiliki banyak konsekuensi pada kehidupan manusia dari segi psikologis. Konsekuensi psikologi yang tidak terdeteksi dini dapat menyebabkan permasalahan dikemudian hari yang dapat mengganggu kehidupan keluarga dan penderitanya, Oleh karena itu perlu adanya alat uji penapisan yang akurat serta handal dalam mendeteksi munculnya gejala psikiatri selama masa isolasi. Penelitian survei yang dilaksanakan di secara virtual melalui google form. Metode ini dipilih karena kondisi Pembatasan Sosial Skala Besar (PSBB) akibat Pandemik Covid-19 yang tidak memungkinkan untuk melakukan wawancara secara tatap muka. Sampel penelitian ini adalah seluruh masyarakat usia produktif dengan kriteria eksklusi berupa data yang tidak lengkap atau tidak bersedia mengikuti penelitian. Penelitian ini merupakan penelitian pendahuluan dari serangkaian proses uji kesahihan dan kehandalan. Analisa uji kesahihan internal menggunakan metode Pearson Product Moment dengan interpretasi bulir pertanyaan dikatakan sahih jika korelasi rho (r) ≥ 0,3. Analisa uji kehandalan menggunakan metode pengujian Cronbach α dengan interpretasi handal bila nilai minimum Cronbach α sebesar 0,6. 281 responden yang memenuhi kriteria inklusi. Hasil pengujian dengan Pearson Product Moment atau Pearson Correlation didapatkan nilai rho (r) pada seluruh bulir pertanyaan adalah diatas 0,3 . Hasil uji kehandalan menggunakan uji Cronbach α adalah 0,935 dengan nilai Cronbach’s Alpha if Item Deleted pada masing-masing bulir dibawah nilai Cronbach α. Cabin Fever Phenomenon (CFP) Versi Indonesia terbukti memiliki kesahihan yang baik serta kehandalan yang sangat baik untuk mendeteksi munculnya gejala psikiatri selama masa isolasi. Perlu dilakukan uji kesahihan lanjutan seperti uji kesahihan eksternal.